Retroperitoneal myxosarcoma in a cat - Haleigh Hixson; Sheryl Coutermarsh‐Ott; Brittany Ciepluch; Katharine Kierski; Kevin Lahmers; Joanne Tuohy (Clinical Case Reports, 2022)
Abstract This report details a retroperitoneal myxosarcoma in a cat that exhibited extremely aggressive biological behavior. An exploratory midline celiotomy revealed a left‐sided retroperitoneal mass firmly adhered to the hypaxial musculature. Histopathological evaluation identified the mass as a myxosarcoma. Following surgical excision, the mass rapidly recurred within 6 weeks after surgery.